PENDEKATAN â EMPAT P â DALAM KEGIATAN PENDIDIKAN DAN PEMBELAJARAN - Fitriani, Aries (IAIN Ponorogo, 2011)
Learning is closely related with how to educate learners and set up the learning process that best suits on the studentsâ need so as to make the process running effectively and meaningfully and learners can encourage themselves achieve the objectives as what is actualized in the curriculum. The scholars and experts in education have been trying to develop various methods and approaches that can be used by educators in the learning process. The teachersâ ability in selecting and determining the approach to learning will greatly impact the effectiveness of learning itself. This article attempts to discuss and explain the concept of a